2016
DOI: 10.1016/j.bbr.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological modulation of lateral habenular dopamine D2 receptors alters the anxiogenic response to cocaine in a runway model of drug self-administration

Abstract: Cocaine has long been known to produce an initial “high” followed by an aversive/anxiogenic “crash”. While much is known about the neurobiology of cocaine’s positive/rewarding effects, the mechanisms that give rise to the drug’s negative/anxiogenic actions remain unclear. Recent research has implicated the lateral habenula (LHb) in the encoding of aversive events including the anxiogenic response to cocaine. Of particular interest in this regard are the reciprocal connections between the LHb and the ventral te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 92 publications
(125 reference statements)
0
9
0
Order By: Relevance
“…Although the LHb has been linked with anxiety-related behaviors (Chan et al, 2016;Dolzani et al, 2016;Pobbe and Zangrossi, 2008;Shelton et al, 2016), its role in the context of ethanol withdrawal was unknown. We found that LHb neurons in ethanol-withdrawn (Post-EtOH) rats had a significantly higher spontaneous firing rate (Li et al, 2016) and excitability, suggesting a possible contribution of LHb hyperactivity to the increased anxiety levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although the LHb has been linked with anxiety-related behaviors (Chan et al, 2016;Dolzani et al, 2016;Pobbe and Zangrossi, 2008;Shelton et al, 2016), its role in the context of ethanol withdrawal was unknown. We found that LHb neurons in ethanol-withdrawn (Post-EtOH) rats had a significantly higher spontaneous firing rate (Li et al, 2016) and excitability, suggesting a possible contribution of LHb hyperactivity to the increased anxiety levels.…”
Section: Discussionmentioning
confidence: 99%
“…That such a mechanism could specify targeting of the DA mesohabenular phenotype suggests an explanation as to why TH expression is retained in an otherwise non-DA projection. Nevertheless, DA receptors are expressed in LHb and appear to play important roles in aversive memory retrieval (Chan et al, 2017), the aversive effects of ethanol (Zuo et al, 2017) or cocaine (Shelton et al, 2016) and cue-induced reinstatement of nicotine seeking (Kaled et al, 2014).…”
Section: Afferent Connectionsmentioning
confidence: 99%
“…This means that the over‐activity in LHb after cocaine self‐administration that was observed in the present study likely represents increased inhibition of dopaminergic neurons, a process that may be associated with aversive effects evoked by cocaine. Dopaminergic and glutamatergic mechanisms in the habenula—besides playing a likely role in the observed increase in c‐fos expression—have been shown to be involved in the aversive effects of cocaine exposure (Jhou et al ., ; Meye et al ., ; Shelton et al ., ). Moreover, it has been demonstrated that intact LHb function is necessary for rats to inhibit responding to cocaine‐associated cues when it is signaled that cocaine is not available (Mahler & Aston‐Jones, ; Zapata et al ., ), although there is no evidence that the habenula is involved in punished cocaine seeking (see Jean‐Richard‐Dit‐Bressel & McNally, ; Zapata et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Brain structures widely implicated in addiction include the prefrontal cortex, striatum, amygdala and the ventral tegmental area (VTA) (Jentsch & Taylor, ; Feil et al ., ; Koob & Volkow, ; Hearing et al ., ; Everitt & Robbins, ; Oliva & Wanat, ). More recently, studies have begun to investigate the role of the lateral habenula (LHb) in addictive behavior, and it has been suggested that this structure is important for the aversive aspects of drug intake (Jhou et al ., ; Meye et al ., ; Shelton et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation